2011
DOI: 10.1007/s11701-011-0325-0
|View full text |Cite
|
Sign up to set email alerts
|

Gestonurse: a robotic surgical nurse for handling surgical instruments in the operating room

Abstract: While surgeon-scrub nurse collaboration provides a fast, straightforward and inexpensive method of delivering surgical instruments to the surgeon, it often results in "mistakes" (e.g. missing information, ambiguity of instructions and delays). It has been shown that these errors can have a negative impact on the outcome of the surgery. These errors could potentially be reduced or eliminated by introducing robotics into the operating room. Gesture control is a natural and fundamentally sound alternative that al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 15 publications
0
23
0
Order By: Relevance
“…One of the more radical, recent initiatives, requiring standardisation in extremis, is the development of the automated scrub nurse that issues implements and materials in response to commands from the surgeon (see for example 'Gestonurse ' Jacob et al 2011, Wachs, et al 2014); a development that is founded, in part, upon the idea that robots are not subject to the performance variation and error sometimes ascribed to surgical assistants. These initiatives reflect the ambivalent standing of the scrub nurse and her or his knowledge and expertise, that skills and competencies of the scrub nurse are 'non-technical' with the role primarily consisting of reading the mind and responding where necessary to the demands of the surgeon.…”
Section: Discussion: Agency Practice and Embodied Actionmentioning
confidence: 99%
“…One of the more radical, recent initiatives, requiring standardisation in extremis, is the development of the automated scrub nurse that issues implements and materials in response to commands from the surgeon (see for example 'Gestonurse ' Jacob et al 2011, Wachs, et al 2014); a development that is founded, in part, upon the idea that robots are not subject to the performance variation and error sometimes ascribed to surgical assistants. These initiatives reflect the ambivalent standing of the scrub nurse and her or his knowledge and expertise, that skills and competencies of the scrub nurse are 'non-technical' with the role primarily consisting of reading the mind and responding where necessary to the demands of the surgeon.…”
Section: Discussion: Agency Practice and Embodied Actionmentioning
confidence: 99%
“…Studies on the application of gesture-based COTS devices in robot-assisted surgery failed to demonstrate usefulness, either due to the high cost of the robotic arm when using commercial cameras in surgical instrumentation (101) and, in the case of the LMC, due to the need for a more robust API (102)(103), or to lack of sufficient accuracy and robustness to manipulate a medical robot (48). However, a simulation study of endonasal pituitary surgery that compared the LMC with the Phantom Omni showed that surgeons achieved a percentage of tumour mass resection and procedure duration very similar to that accomplished with the robot using the LMC (104).…”
Section: Discussionmentioning
confidence: 99%
“…The use of robots as an assistant in hospitals is has seen an increase Proceedings of the IEEE SoutheastCon 2015, April 9 -12, 2015 -Fort Lauderdale, Florida 978-1-4673-7300-5/15/$31.00 ©2015 IEEE 300-5/15/$31.00 ©2015 IEEE lately. 'Gestonurse' is a robot assistant to help the surgeon in the operating room (OR) by passing surgical instruments [27] [28]. Speech and gesture can be used to control the robot operations.…”
Section: Medicinementioning
confidence: 99%
“…Speech and gesture can be used to control the robot operations. Figure 5 [27] shows the robotic scrub nurse Gestonurse assisting in the OR.…”
Section: Medicinementioning
confidence: 99%